Tingkat Pemahaman Akuntansi (Studi Mahasiswa Jurusan Akuntansi FEB UNTAN) - Indra, Sukma; Rusmita, Sari (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2018)
The research is aimed at observing the comprehension level of accounting students in accounting course, the class program and gender. Purposive sampling was used as the sampling technique, in which the students who had taken PA1, PA2, AKM1 and AKM2 courses were the research sample. The hypothesis was answered by one sample T-Test to assess the comprehension level of accounting students, while One Way ANOVA was employed to examine the possible difference of students in Regular A, PPAPK and International classes in comprehending accounting course. Furthermore, independent sample test was used to observe the comprehension level based on gender.There were three research findings. First, there is a different comprehension level of accounting students in accounting department of all programs, namely Regular A, PPAPK and International classes. It might be caused by the quality of different student input, because they have different entrance on every program. Second, there is no difference in comprehension level of accounting students based on gender.